2019
DOI: 10.1155/2019/1704650
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Oxidative Stress Elevates Arginase 1 and Uncoupled Nitric Oxide Synthesis in Skeletal Muscle of Aged Mice

Abstract: Aging is associated with reduced muscle mass (sarcopenia) and poor bone quality (osteoporosis), which together increase the incidence of falls and bone fractures. It is widely appreciated that aging triggers systemic oxidative stress, which can impair myoblast cell survival and differentiation. We previously reported that arginase plays an important role in oxidative stress-dependent bone loss. We hypothesized that arginase activity is dysregulated with aging in muscles and may be involved in muscle pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…Increased arginase activity may be the result of mild, sustained oxidative stress in βThal + traits, as observed in normal aging [ 51 ], and a compensatory defense mechanism against the NOS-associated oxidative/nitrosative stress. In either case, it may contribute to the resistance of βThal + RBCs to malaria infection, since the host arginine (intracellular and introduced by RBC amino acid transporters) is metabolized by the parasite to sustain its metabolic needs [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased arginase activity may be the result of mild, sustained oxidative stress in βThal + traits, as observed in normal aging [ 51 ], and a compensatory defense mechanism against the NOS-associated oxidative/nitrosative stress. In either case, it may contribute to the resistance of βThal + RBCs to malaria infection, since the host arginine (intracellular and introduced by RBC amino acid transporters) is metabolized by the parasite to sustain its metabolic needs [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using models of aging and CVD have shown that endothelial Ar competes for L-arginine reducing eNOS activity and therefore, decreasing NO bioavailability ( Pandya et al, 2019 ; Shin et al, 2012 ; Zhu et al, 2017 ). On the other hand, Ar inhibition improves endothelial function in elderly healthy subjects ( Mahdi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Arg1 levels gradually increase in skeletal muscles of mice during aging [ 142 ], nevertheless, its upturn is not followed by elevation in polyamine levels. This phenomenon may reflect a compensatory mechanism, which in any case is inadequate to support the polyamine content in aged organism, and causes arginine deficiency, NOS and ADC substrate deprivation.…”
Section: Evolutionary Perspective On Aging and Alzheimer's Diseasementioning
confidence: 99%